2015
DOI: 10.1101/gad.263202.115
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 cooperates with the SWI/SNF chromatin remodeling complex to regulate VEGFR2 in breast cancer cells

Abstract: Mutant p53 impacts the expression of numerous genes at the level of transcription to mediate oncogenesis. We identified vascular endothelial growth factor receptor 2 (VEGFR2), the primary functional VEGF receptor that mediates endothelial cell vascularization, as a mutant p53 transcriptional target in multiple breast cancer cell lines. Up-regulation of VEGFR2 mediates the role of mutant p53 in increasing cellular growth in two-dimensional (2D) and three-dimensional (3D) culture conditions. Mutant p53 binds nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 73 publications
10
119
0
Order By: Relevance
“…Hence, TP53 mutations may lead to attenuation of immune responses, which can be recovered, at least in some models, with dendritic cell treatment together with antiangiogenesis agents. Expression analyses have demonstrated that VEGFR2 upregulation may be another mechanism by which mutant p53 controls angiogenesis (30). VEGFR2 is a receptor tyrosine kinase activated by binding of the VEGF-A ligand, and it is the main receptor mediating endothelial cell neovascularization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, TP53 mutations may lead to attenuation of immune responses, which can be recovered, at least in some models, with dendritic cell treatment together with antiangiogenesis agents. Expression analyses have demonstrated that VEGFR2 upregulation may be another mechanism by which mutant p53 controls angiogenesis (30). VEGFR2 is a receptor tyrosine kinase activated by binding of the VEGF-A ligand, and it is the main receptor mediating endothelial cell neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TP53 mutational status was also shown to be predictive of response to the VEGFR inhibitor pazopanib in advanced sarcomas (45). The underlying mechanism of response may relate to TP53 mutations being associated with upregulation of VEGF-A and VEGFR2 expression (7,(30)(31)(32). Of interest in this regard, other tumor suppressors that are not directly druggable may also be actionable based on the upregulation of affected pathways when the suppressor gene is mutated (46).…”
Section: Discussionmentioning
confidence: 99%
“…Although effects of wtp53 are primarily mediated by sequence-specific DNA binding to cognate p53 response elements located in regulatory regions of p53 target genes, this DNA binding is commonly prevented by cancer-associated missense mutations clustered in the DNA binding domain. Nevertheless, mutp53 has a broad effect on gene expression profiles by binding genes indirectly through interactions with other transcription factors; for example p63/p73, Sp1/Sp3, NF-Y, ETS2, vitamin D receptor, or SREBP2 (4), and by regulating chromatin-modifying enzymes such as the ATP-dependent nucleosome remodeling complex SWI/SNF and the histone H3 lysine 4 methyltransferases MLL1 and MLL2 (14,16,17). By increasing the expression of various receptor tyrosine kinases (RTKs), such as transforming growth factor β (TGFβ) receptor, epidermal growth factor receptor (EGFR), hepatocyte growth factor receptor (HGFR/c-MET), and plateletderived growth factor (PDGF) receptor β, mutp53 enhances proinvasive signaling, which is further reinforced by stimulatory effects of mutp53 on integrin/RCP-driven receptor recycling (18)(19)(20)(21).…”
mentioning
confidence: 99%
“…The TP53 mutation at codon 249 (R249S) could induce the transcription of MLL and the association with the switch/sucrose non-fermentable nucleosome remodeling complex [20]. In addition, R249S mutation could induce the transcription of SET domain bifurcated 1 (SETDB1), which is known as a histone H3 lysine 9 (H3K9) methyltransferase; SETDB1 could also suppress the degradation of the R249S mutation and play a role in hepatocarcinogenesis [21].…”
Section: Association Between Mutation Of Cancer-related Genes and Epimentioning
confidence: 99%